Prometheus - Scott, Ridley; Rapace, Noomi, 1979-; Fassbender, Michael, 1977-; Theron, Charlize (Beverly Hills, Calif. : Twentieth Century Fox Home Entertainment, 2012)
Explorers discover a clue that may point to the origins of mankind on Earth and leads them to a distant planet.
Noomi Rapace, Michael Fassbender, Charlize Theron, Idris Elba, Guy Pearce.
MPAA rating: R.
DVD, Dolby digital 5.1.
In English, French, or Spanish with optional English, French, or Spanish subtitles.
Closed-captioned.
Keywords: Human beings -- Origin -- Drama; Human-alien encounters -- Drama; Scientists -- Drama; Androids -- Drama; Interplanetary voyages -- Drama; Action and adventure films; Fiction films; Video recordings for the hearing impaired; Thriller films; Feature films; Science fiction films